Approximation Theory on Summability of Fourier Series - Mukherjee, Sanjay; J Khan, A (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
The results of Chandra to (e,c) means U.K.Shrivastava and S.K.Verma have proved the following theorem THEOREM : Let . Then , Where is nth (e, c) means of fourier series of f at x. In this paper we obtain the Fourier series by (N,p,q)(E,1) which is the analogues to the (e , c) means given above .The theorem is as follows THEOREM: Let and be the positive monotonic, non increasing sequence of real numbers be summable (N,p,q)(E,1) to f(x) at the point t=x is